Characterization of AlXGa1−XN/GaN High Electron Mobility Transistor Structures with Mercury Probe Capacitance–Voltage and Current–Voltage. Issue 4 (29th January 2022) - Tucker, Eric; Ramos, Frank; Frey, Samuel; Hillard, Robert J.; Horváth, Péter; Zsákai, Gyula; Márton, Attila
Abstract : Characterization of high electron mobility transistor (HEMT) structures is important for predicting device behavior, monitoring and developing processes, and improving performance. Multifrequency capacitance–voltage (CV) and direct current–voltage (IV) methods are applied with a mercury probe to assess the HEMT with and without capping layers to monitor critical parameters such as pinch‐off voltage, two‐dimensional electron gas (2DEG) sheet charge, GaN carrier density profile, AlGaN thickness, and dielectric constant and properties of the top capping layer. Abstract : Characterizing high electron mobility transistor (HEMT) devices without the need for external processes can be extremely valuable. Using a high precision Hg Capacitance–Voltage (C–V) tool with C–V and Current–Voltage (I–V) capability, many important HEMT parameters can be determined. Multiple cases are illustrated: varying Al mole fraction ratio and Al thickness, a SiN capping layer, and a high resistivity substrate.